Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum - Hutama, Arya Rizky (Journal of Comprehensive Science, 2025)
The existence of land is an integral part of human life that cannot be separated. Land has a very vital role for all human life on earth. To improve the quality of human life, development is a necessity. At this time, the demand for land as a capital asset is increasing along with the increase in development activities. The government really needs land for planned project locations to encourage development, both for the interests of the government and the business sector. The government has issued various policies in the context of land acquisition for development purposes. Land acquisition is an activity to obtain land by providing fair and just compensation to the entitled party. Land acquisition for public interest aims to provide land for the implementation of development in order to improve the welfare and prosperity of the nation, state, and society while still guaranteeing the legal interests of the entitled party. Land acquisition activities need to be carried out quickly, accurately, and openly. Thus, policies related to land acquisition meet the criteria of procedural justice. After compensation is received by the affected parties, land acquisition is declared complete.